POTENSI ATRAKSI WISATA FUN TUBING DI KAWASAN OBJEK WISATA BENDUNG ANAI KORONG SAKAYAN NAGARI PASIELAWEH KABUPATEN PADANG PARIAMAN - Tusadiah, Halimah; Waryono, Waryono; Ferdian, Feri (Journal of Home Economics and Tourism, 2017)
This study aims to determine the potential of fun tubing attraction in the area of the tourist attractionweir Anai Korong Sakayan Nagari Pasielaweh district Padang Pariaman with an indicator of natural resources, location, culture, and entertainment seen from the scenery an water in natural resources, location and area of the location, washing and bathing in culture, experience and games from entertaiment. This research is a qualitative descriptive reseach with qualitative method. Data collection techigue is done by, interview method, observasi, documentation involving informant by using purposive sampling technique. the The results of the study note that potential of fun tubing attractions can be: 1) natural resources have the potensial of natural secenery is still natural example of hills and paddy fields. constraints that often experienced in fun tubing tourist attraction is the unstable water disharge. 2) The location of fun tubing tourist attraction area of anai Korong Sakayan Nagari Pasielaweh district Padang Pariaman. the location of this fun tubing tourist attractions in very strategis because it is close together to other tourist attraction. 3) cultural life of the local community still utilize the natural values that exist in the river such as rocks and sand but it also utilizes other natural resources that exist. 4) the excitement of playing water by following the flow of the flowing river and test adrenaline of the tourists who play fun tubing.keywords: potential, attractions, tours, tourist attraction, fun tubing